GENOME-WIDE ASSOCIATION STUDY IDENTIFIED QTLS FOR BEHAVIORAL TRAITS IN KOREAN SAPSAREE DOGS - Md Azizul Haque; Na-Kuang Kim; Ryu Yeji; Bugeun Lee; Ji-Hong Ha; Yun-Mi Lee; Han-Kook Il; Jong-Joo Kim (Journal of Animal and Plant Sciences, 2025)
This study aimed to identify QTL and nearby candidate genes influencing behavioral traits within the Korean Sapsaree dog population. Phenotypic data for three key behavioral traits – emotion, companion, and training were collected from 378 dogs, of which 234 individuals were genotyped using the 170k Illumina CanineHD BeadChip. Genome-wide association studies (GWAS) was performed using a univariate linear mixed model (LMM) implemented in the genome-wide efficient mixed-model analysis (GEMMA) software. The analysis identified 40 significant SNPs associated with these behavioral traits. Specifically, 15 significant sites were identified within CFA27 and CFA38 for emotion, 17 significant genomic regions across CFA1, CFA19, and CFA38 were noted for companionship behavior, and training behavior was associated with 8 significant regions within CFA7 and CFA21. Interestingly, several associated sites were found in or near genes linked to neuropathology or neuronal functions, including FGD4, OVCH1, and EIF2D, which are associated with emotion. Additionally, four neuronal-related genes, NMBR, ADGRG6, HIVEP2, and PTPN4, have been identified as influencing companion behavior. Significant variants impacting trainability were located within the GREM2 and SWAP70 genes. This study significantly advances our knowledge of the genetic architecture of behavior in Korean Sapsaree dogs, offering valuable insights into canines.
Keywords: Behavioral traits; Candidate genes; Canine; Korean Sapsaree; SNP